Pengembangan LKPDD IPAS Berbasis Role Playing pada Kelas IV Materi Kegiatan Jual Beli SDN Sukolilo Barat 1 - Indrastuti Ratih Fidela; Widya Trio Pangestu (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Research was motivated by low fourth-grade IPAS learning outcomes at SDN Sukolilo Barat 1, where the first-semester summative average was only 34% due to conventional methods and limited innovative materials. Conversely, needs analysis showed 85% of students prefer playful activities. This study aims to develop a valid, effective, and engaging role-playing-based student worksheet (LKPD) for fourth-grade IPAS on buying and selling activities. Using the Research and Development (R&D) method with the 4D model, data were collected via interviews, observations, questionnaires, and 10 pre-test and post-test essay questions. Product feasibility was validated by material, learning resources, and instructional design experts. Product trials involved 9 small-group and 15 large-group students using a one-group pre-test–post-test design, analyzed via Paired Sample T-test and Normalized Gain (N-Gain). The study successfully developed a role-playing-based LKPD on economic activities aligned with the Merdeka Curriculum. Through a learning-by-doing approach, this LKPD accommodates diverse learning characteristics (kinesthetic, visual, audio-visual) to improve cognitive outcomes and create interactive, meaningful learning experiences.